Determination of Cu, Mn, and Pb in yogurt samples by flame atomic absorption spectrometry using dry, wet, and microwave ashing methods - Kaya, Gokce; Akdeniz, Ismail; Yaman, Mehmet (Atomic Spectroscopy Press Ltd, 2008)
The digestion procedures based on dry and wet ashing and closed vessel-assisted microwave oven were compared to determine a rapid, reliable, and simple digestion method for the flame atomic absorption spectrophotometric analysis of yogurt samples. Various temperatures and periods for dry ashing, various amounts of the digesting mixture/sample for wet ashing, and different powers of the microwave oven were examined. The obtained data show that the microwave oven is an excellent method because it is fast and results in fewer losses and contaminants. In dry ashing, considerable lead losses were observed when 500 degrees C was applied for a period of eight hours. The results were compared with those reported in the literature. It was found that the Pb concentration of all studied samples (except for two samples-taken from top of Al container) were higher than the maximum limit (20 ng g(-1)) set by FAO/WHO for milk.
Keywords: Trace-Elements; Milk; Sensitivity; Digestion; Copper; Fe